2015
DOI: 10.1155/2015/812035
|View full text |Cite
|
Sign up to set email alerts
|

GABABEncephalitis: A Fifty-Two-Year-Old Man with Seizures, Dysautonomia, and Acute Heart Failure

Abstract: Autoantibodies to the γ-aminobutyric acid receptor, subtype B (GABAB), are a known cause of limbic encephalitis. The spectrum of clinical manifestations attributable to this antibody is not well defined at the present time. Here we present a case of GABAB encephalitis presenting with encephalopathy, status epilepticus, dysautonomia, and acute heart failure. To our knowledge, heart failure and dysautonomia have not yet been reported with this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…As previously reported, LE can lead to autonomic dysfunction via the connection between the medial temporal lobe and insular cortex [16, 17]. Loftspring et al , reported a case of anti-GABA-B receptor encephalitis with cardiac autonomic dysfunction [18]. However, gastrointestinal autonomic dysfunction has not yet been reported in patients with anti-GABA-B receptor encephalitis.…”
Section: Discussionmentioning
confidence: 96%
“…As previously reported, LE can lead to autonomic dysfunction via the connection between the medial temporal lobe and insular cortex [16, 17]. Loftspring et al , reported a case of anti-GABA-B receptor encephalitis with cardiac autonomic dysfunction [18]. However, gastrointestinal autonomic dysfunction has not yet been reported in patients with anti-GABA-B receptor encephalitis.…”
Section: Discussionmentioning
confidence: 96%